Choice of techniques: an aspect of the theory of planned economic development. - Sen, Amartya (Oxford, Blackwell, 1968)
Discussion of the nature of problem on consumer goods and the production of capital goods by unassisted labour.
Bibliography: p. xxvii-xxix.
sju 23/01/2019
Loans
Keywords: Industrial management; Machinery in the workplace; Labor productivity; Developing countries